Energy savings by smart utilization of mechanical and natural ventilation for hybrid residential building model in passive climate - Homod R.Z.; Sahari K.S.M. (2023)
This paper focuses on the efficiency of controlling building internal temperature and relative humidity by ventilation and infiltration flow rate. Building model is inevitable to study the feasibility of building ventilation, and how it affects the indoor air quality. A hybrid model is built using physical and empirical functions of subsystems model, where the empirical function being the residential load factor (RLF) used to calculate the cooling/heating load depending on the indoor/outdoor temperature. Furthermore, by using the RLF method, the parameters of the model can be calculated room by room, which is appropriate for variable air volume (VAV). The subsystem modeling approach chosen divides the building into four components, which are closely related to the indoor thermal comfort. Indoor thermal comfort represented by predicted mean vote (PMV) can be represented by temperature, indoor air velocity and relative humidity which are controlled by the HVAC system. Response sensitivity analysis is carried out on the main parameters of the model by applying real climate conditions data for a passive climate. Simulations with varied flow rate mechanical ventilation are conducted within 24 h. Results indicate that there is a great opportunity to take advantage of mechanical ventilation to help achieve thermal comfort while reducing the dependency on powered cooling. 2012 Elsevier B.V.